Atomically thin cesium lead bromide perovskite quantum wires with high luminescence. Issue 1 (9th December 2016) - Huang, Hongwen; Liu, Mei; Li, Jing; Luo, Laihao; Zhao, Jiangtao; Luo, Zhenlin; Wang, Xiaoping; Ye, Zhizhen; He, Haiping; Zeng, Jie
Abstract : Atomically thin CsPbBr3 quantum wires with a high quantum yield of 21.13% were demonstrated and understood. Abstract : We report a room-temperature colloidal synthesis of few-unit-cell-thick CsPbBr3 QWs with lengths over a hundred nanometers. The surfactant-directed oriented attachment growth mechanism was proposed to explain the formation of such CsPbBr3 QWs. Owing to the strong quantum confinement effect, the photoluminescence (PL) emission peak of few-unit-cell-thick CsPbBr3 QWs blue-shifted to 430 nm. The ensemble PL quantum yield (PLQY) of the few-unit-cell-thick CsPbBr3 QWs increased to 21.13% through a simple heat-treatment process. The improvement of PLQY was ascribed to the reduction of the density of surface trap states and defect states induced by the heat-treatment process. Notably, the dependence of the bandgap on the diameter with different numbers of unit cells was presented for the first time in 1-D CsPbBr3 QWs on the basis of the produced few-unit-cell-thick CsPbBr3 QWs.